2011
DOI: 10.1007/s00246-011-0143-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Risk Factors for Korean Children with Kawasaki Disease

Abstract: Kawasaki disease (KD) is the most common cause of acquired heart disease in children. Intravenous immunoglobulin (IVIG) is the standard therapy for KD, but more than 10% of KD patients do not respond to IVIG and are at high risk for the development of coronary artery lesions (CALs). To identify clinical and genetic risk factors associated with CAL development and IVIG nonresponsiveness, this study analyzed the clinical data for 478 Korean KD patients. Multivariate logistic regression analysis showed that incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 34 publications
8
25
0
Order By: Relevance
“…It has been reported that higher CRP, higher maximum platelet, lower albumin, or lower hemoglobin values are associated with IVIG-non responsiveness and the risk of CALs [28][29][30][31]. Our laboratory results provided evidence of changing epidemiology in KD in Korea, and this may be the first laboratory-proven study to demonstrate the results.…”
Section: Discussionsupporting
confidence: 66%
“…It has been reported that higher CRP, higher maximum platelet, lower albumin, or lower hemoglobin values are associated with IVIG-non responsiveness and the risk of CALs [28][29][30][31]. Our laboratory results provided evidence of changing epidemiology in KD in Korea, and this may be the first laboratory-proven study to demonstrate the results.…”
Section: Discussionsupporting
confidence: 66%
“…However, it is still unknown how long anemia persists in patients with KD. Elevated inflammatory markers and IVIG nonresponsiveness may be associated with the development of CAL in KD [34]. Our study demonstrated that a lower decrease in hepcidin levels after IVIG treatment was associated with the occurrence of CAL and resistance to IVIG treatment.…”
Section: Discussionmentioning
confidence: 50%
“…Increased levels of Pellino-1 and Pellino-2 were found in patients with asthma (110), and kidney transplant recipients experiencing acute rejection showed increased Pellino-2 mRNA levels (111), while Pellino-3 expression is downregulated in the colon of patients with Crohn's disease (67). Interestingly, Pellino-1 SNPs have been linked to increased risks of coronary artery lesions in children with Kawasaki disease, a rare form of vasculitis (112,113). Furthermore, patients with diffuse large B-cell lymphomas showed a close correlation between increased expression of Pellino-1, increased levels of BCL6, and poor prognosis (106).…”
Section: Pellinos and Diseasementioning
confidence: 99%